ANALYSIS OF THE FACTORS CAUSING DIFFICULTIES IN SPEAKING ENGLISH FOR GRADE 10 STUDENTS OF SMA ISLAM PAGERUNGAN BESAR - Masyhuri (JPGENUS: Jurnal Pendidikan Generasi Nusantara, 2024)
This study aims to analyze the factors causing difficulties in speaking English grade 10 students at SMA Islam Pagerungan Besar. The ability to speak English is very important where in this era, English is the language used in international communication. However, there are still many 10 grade students at SMA Islam Pagerungan Besar who have difficulties in speaking English. This study uses a qualitatve method with case study approach, data were collected through interviews, classroom observations, and analysis of related documents. The results of the study indicate that there are 2 main factors causing difficulties experienced by students, namely internal and external factors. Internal factors include lack of confidence, limited vocabulary mastery, difficulty in pronunciation, afraid of making mistakes, and lack of motivation. Meanwhile, external factors include less supportive environment, learning facilities are inadequate, less effecttive teaching methods, lack of support from teacher and friends, and lack of opportunity to practice speaking. Based on these findings, it is suggestions that teachers and school create more supportive learning environment to increase students’ self-confidence, provide more opportunities for students to practice speaking through activities outside the classroom, and use more interactive and innovative teaching methods. In addition, improving learning facilities such as providing language laboratories and digital learning resources, as well as providing books on speaking skills are needed to help students improve their English speaking skills.